2019
DOI: 10.1111/phn.12622
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative assessment of a dog program for youth offenders in an adult prison

Abstract: Objective Dog programs occurring in prison tend to generate positive public opinion and media portrayals, yet they often lack empirical validation. This is the first study to examine the key themes that drive a dog program aimed at incarcerated youth serving time in an adult prison. Design and Sample A sample of male youth (n = 31) were provided survey questions on a rescue dog program. A grounded qualitative approach was employed with open‐ended responses. Results The following themes emerged: the symbolism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…For incarcerated adolescents in particular, positive rehabilitating effects have been reported in studies with a qualitative design (e.g., Leonardi et al, 2017; Smith & Smith, 2019), suggesting DTPs may be promising for youth offenders. However, controlled studies focusing on DTPs for this group are scarce: the recent meta-analysis (Duindam et al, 2020) included only three studies that were conducted on incarcerated youth (e.g., Chianese, 2009; Grommon et al, 2018; Seivert et al, 2016) and these reported mixed findings about the DTP’s effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…For incarcerated adolescents in particular, positive rehabilitating effects have been reported in studies with a qualitative design (e.g., Leonardi et al, 2017; Smith & Smith, 2019), suggesting DTPs may be promising for youth offenders. However, controlled studies focusing on DTPs for this group are scarce: the recent meta-analysis (Duindam et al, 2020) included only three studies that were conducted on incarcerated youth (e.g., Chianese, 2009; Grommon et al, 2018; Seivert et al, 2016) and these reported mixed findings about the DTP’s effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, four articles [ 18 , 32 , 56 , 57 ] (20% of the total) evaluated both female and male inmates; one of them [ 18 ] was developed in a psychiatric prison. Additionally, four articles [ 45 , 46 , 58 , 59 ] (20% of the total) investigated young inmates.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 displays the study design in each for the selected articles. A total of 14 (70% of the total) articles were classified as observational studies (an experimental group that was only assessed once at the end of the intervention) [ 14 , 18 , 39 , 44 , 48 , 49 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. Of them, seven (50%) followed a quantitative [ 18 , 39 , 48 , 49 , 54 , 56 , 57 ] and seven (50%) a qualitative methodology [ 14 , 44 , 52 , 53 , 55 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations